Early prediction of pathological response to neoadjuvant chemotherapy of breast tumors: a comparative study using amide proton transfer-weighted, diffusion weighted and dynamic contrast enhanced MRI - Zhang, Nan; Song, Qingwei; Liang, Hongbing; Wang, Zhuo; Wu, Qi; Zhang, Haonan; Zhang, Lina; Liu, Ailian; Wang, Huali; Wang, Jiazheng; Lin, Liangjie (Frontiers in Medicine, 2024)
Objective To examine amide proton transfer-weighted (APTw) combined with diffusio weighed (DWI) and dynamic contrast enhanced (DCE) MRI for its value for earl prediction of pathological response to neoadjuvant chemotherapy in invasive breas cancer.In this prospective study, 50 female breast cancer patients (49.58±10.62 year old) administered neoadjuvant chemotherapy (NAC) were enrolled with MRI carried ou both before NAC (T0) and at the end of the second cycle of NAC (T1). The patients wer divided into 2 groups based on tumor response according to the Miller-Payne Gradin (MPG) system. Group 1 included patients with a greater degree of decrease in majo histologic responder (MHR, Miller-Payne G4-5), while group 2 included non-MHR case (Miller-Payne G1-3). Besides tTraditional imaging protocols (T1WI weighted, T2W weighted, T2WI, DWIdiffusion weighted, and DCEDCE-MRI imaging) and, APTw images were reconstructed by the quantification of magnetization transfer ratio b asymmetric analysis at +3.5 ppm.imaging were scanned for each subject before and afte treatment. APTw value (APTw0 and APTw1), Dmax (maximum diameter, Dmax0 an Dmax1), V (3D tumor volume, V0 and V1), and ADC (apparent diffusion coefficien ADC0 and ADC1) before and after treatment, as well as changes between the two time points (ΔAPT, ΔDmax, ΔV, ΔADC) for breast tumors were compared between the tw groups.APTw imaging hasalong with change of tumor size showed a significan potential clinical value in early prediction of MHR for NAC treatment in breast cance which might allow timely regimen refinement before definitive surgical treatment.